The Analysis of Knowledge, Attittude, and Practical Political Technique - Emiliana Manek (Jurnal Penelitian Humaniora, 2015)
This study was aimed at determining the knowledge, attitudes, and skills of women in Belu, barriers to women's political participation and efforts to increase women's political participation in Belu. The aspects used in this research method are the type of research, the research approach, research setting, research schedule, the subject of research, data collection techniques, data analysis techniques, and data validity. The results show that the low participation of women in politics Belu was in luenced by the internal and external factors. The internal factor is the poor quality of women's resources in terms of knowledge, attitude and skills of practical political technique. While the external factors include: political and institutional barriers, cultural barriers patriarchy, socio-economic barriers, and so forth